Publication Status of Graduate Theses of Internal Disease Nursing: A Systematic Review - Songül Karadağ; Ecem Özgül; Gülsüm Nihal Çürük (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: Transforming master's theses into publication is important for sharing scientific knowledge.Aim: This study was conducted to determine the conversion rate of internal medicine nursing master's theses made in Turkey into scientific articles.Method: Between December 2019 and February 2020, the thesis database of the Council of Higher Education of the Republic of Turkey was used. All master theses are held, as a legal requirement, and were searched for "Internal Medicine Nursing" and "Nursing" master theses completed between 2004 and 2018. The publication rate of these theses was found by searching for the names of thesis author and supervisor on the following databases: PubMed, Thomson Reuters Web of Science, Google Scholar, Turkish Medline, and Turkish Academic Network and Information Center National Academic Network.Results: More than thirty (31.4%) of 616 theses included in the study were published in Science Citation Index, Science Citation Index Expanded and Social Sciences Citation Index, 3.5% in Emerging Sources Citation Index, 25.0% in other international refereed journals, 19.9% in national academic network and information center, and 20.2% in other national refereed journals.Conclusion: It was determined that less than half of the master's theses in the field of internal medicine nursing were published and that, of these published theses, less than half appeared in journals covered by Science Citation Index, Science Citation Index Expanded, or Social Sciences Citation Index. Solutions must be generated to promote the Science Citation Index, Science Citation Index Expanded, or Social Sciences Citation Index publication of master theses.